RANCANG BANGUN QUIZ APP BERBASIS WEB SEBAGAI MEDIA EVALUASI PEMBELAJARAN DI SMK TARUNA PADANG - Hanif, Insan Matin; Zaus, Mahesi Agni; Delianti, Vera Irma; Budayawan, Khairi (Jurnal Publikasi Manajemen Informatika, 2026)
This study is motivated by the fact that many vocational high schools in Indonesia still rely on paper-based examinations despite the growing adoption of digital learning evaluation. At SMK Taruna Padang, examinations for around 100 active students are still conducted manually, although the school only employs 17 teachers, resulting in a heavy correction workload, repeated printing costs, and the absence of immediate feedback for students. This study aimed to design and build a web-based quiz application equipped with a reusable question bank and an analytics dashboard as a learning evaluation medium for SMK Taruna Padang. The system was developed using the Waterfall method and built with the Laravel framework and a MySQL database. The application provides three access roles, namely administrator, teacher, and student, and integrates automatic scoring with a dashboard that visualizes score distribution, question difficulty level, and class performance. System functionality was verified through Black Box Testing on 47 scenarios, all of which produced successful results, while feasibility was assessed by three media validators, yielding a feasibility score of 95.33 percent in the very feasible category. These findings indicate that the developed quiz application is feasible for implementation as a practical alternative to conventional paper-based examinations in vocational schools